Índice de qualidade dos serviços de abastecimento de água no Brasil: concepção, avaliação e aplicação - Otávio Henrique Campos Hamdan (2024)
The use of performance indicators for monitoring processes is widespread in different fields. In water supply systems, indicators can be used to assess efficiency, efficacy and effectiveness, from the collection to the delivery of water to the consumer. In order to assess the quality of the water supply service using a single index, this thesis proposes the Service Quality Index (IQS) using indicators available in the National Sanitation Information System (SNIS). In a complementary way, based on this index, the intention was to evaluate the relationship between service quality and factors such as location, population size and human development. Furthermore, extending its application, this study also presents a specific index for the regulatory sector, in order to prioritize inspections of water supply services. To achieve this goal, the methodology for creating the indices was based on multi-criteria analysis and comprised seven main stages: (i) pre-selection of indicators, (ii) grouping of indicators according to typology, (iii) screening of indicators, (iv) establishment of evaluation scales, (v) evaluation of the relative importance of typologies and indicators - Analytic Hierarchy Process (AHP), (vi) determination of the index, and (vii) calculation of the index for the desired context. In order to assess the relationship between service quality and factors such as location, population size and human development, statistical comparison tests (specifically Kruskal-Wallis followed by multiple comparisons) and descriptive data analysis were used. As a result, the IQS was created with 11 indicators on the water supply service, with the water supply service coverage index (IN055) having the greatest weight in the index (20.0%). Based on the IQS, 4,654 Brazilian municipalities were evaluated, with 25.03% showing excellent performance and 49.35% good performance. In all the comparisons of the IQS by grouping, there was some significant difference in the median of the groups, when clustering by states, geographic regions, hydrographic regions, population groups or classifications in relation to the Municipal Human Development Index (IDHM). Finally, with the replication of the methodology for the regulatory sector, the Regulatory Quality of Service Index (IRQS), which included 12 indicators, was created. The most relevant indicator was the water supply coverage index in the concession area (weight of 17.2% in the IRQS). These results open up the possibility of assessing the quality of water supply services using a unified index that captures different aspects of service delivery. In addition, it is expected that this thesis inspires the development of indices for other contexts of basic sanitation and that the findings of this study underpin the creation of public policies to improve the water supply service provided in Brazilian municipalities.